Pengembangan Biobriket Dari Limbah Kulit Nangka Muda (Artocarpus Heterophyllus Lamk.) Dengan Berbagai Konsentrasi Bahan Perekat Dari Tepung Tapioka - Arzita, Arzita; Fathia, Nyimas Myrna Elsa; Fitriani, Miranti Sari; Ikawati, Diyan; Nizori, Addion (Universitas Batanghari, 2024)
Young jackfruit waste accounts for around 70% of its total weight in the form of skin and straw, which is typically discarded, indicating that it has the potential to damage the environment. Young jackfruit skin waste comprises lignocellulose, including cellulose (38.69%), hemicellulose (20.80%), lignin (26.50%), and water (11.13%). This composition is most likely to be utilised as biological charcoal as a raw material for the production of Biobriquettes, which are a valuable renewable energy source. The objective of this research is finding the best concentration of tapioca adhesive for manufacturing Biobriquettes from juvenile jackfruit skin. The research was carried out at the Agricultural Engineering Laboratory.The research is divided into five stages: preparation of young jackfruit skin waste, carbonisation and sieving process, adhesive manufacturing, biobriquette making, and biobriquette printing. The study used a Completely Randomised Design with four (four) treatments and five (five) replications, specifically administering tapioca adhesive concentrations (25%, 30%, 35%, and 40%). The parameters observed include water content, ash content, volatile substances, resistance, initial flame time and flame duration.The research Data were analysed using ANOVA, followed by Duncan's New Multiple Range Test at the 5% level. The best biobriquette results were obtained by utilising a concentration ratio of young jackfruit peel charcoal and adhesive of (75:25%), with a water content of 5.16%, ash content of 7.96%, volatile compounds of 12.29%, durability of 0.40%, time The initial flame lasted 6.33 minutes, while the flame duration was 113.98 minutes. These results comply with Indonesian National Standards (SNI 01-6325-2000)Â Â